2020
DOI: 10.1136/bmjdrc-2020-001292
|View full text |Cite
|
Sign up to set email alerts
|

HbA1c response and hospital admissions following commencement of flash glucose monitoring in adults with type 1 diabetes

Abstract: IntroductionOur aim was to assess the effect of introducing flash monitoring in adults with type 1 diabetes with respect to change in hemoglobin A1c (HbA1c) and frequency of hospital admissions.Research design and methodsProspective observational study of adults with type 1 diabetes in our center, in whom a prescription for a flash monitoring sensor was collected. Primary outcome was change in HbA1c between 2016 and after flash monitoring. Rates of hospital admission were compared between the first year after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 15 publications
3
18
0
Order By: Relevance
“…Stimson et al explored the change in HbA1c and the rates of hospital admission following FSL monitoring in people with T1DM and reported a median fall in HbA1c of 1 mmol/mol over a median duration of 38 weeks while observing no change in overall hospital admissions. 18 In this study, DAFNE attendance was among the factors associated with a greater fall in HbA1c. However, as this was a univariate analysis and was not adjusted for other variables (baseline HbA1c, age, gender, etc), it should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Stimson et al explored the change in HbA1c and the rates of hospital admission following FSL monitoring in people with T1DM and reported a median fall in HbA1c of 1 mmol/mol over a median duration of 38 weeks while observing no change in overall hospital admissions. 18 In this study, DAFNE attendance was among the factors associated with a greater fall in HbA1c. However, as this was a univariate analysis and was not adjusted for other variables (baseline HbA1c, age, gender, etc), it should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 56%
“…Several studies have demonstrated improved glycaemic control with FSL use, which was reported to be greater in people with higher pre-FSL HbA1c levels and the number of FSL scans over 14 days. [15][16][17][18][19][20] In a large observational study, we have previously shown that FSL use is associated with improved glycaemic control and hypoglycaemia awareness among other clinically beneficial outcomes. However, on linear regression modelling, structured education was not a significant factor in the reduction of HbA1c (β=0.82, p=0.090).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, median (IQR) GCS on arrival was also lower among incidents stratified as T1DM 13. [9][10][11][12][13][14][15] All mean pulse rates were within the normal physiological range, and seizure rates were significantly higher in type 1 diabetes 1.1% (n = 17) compared with type 2 diabetes 0.3% (n = 4).…”
Section: Vital Signs and Symptomsmentioning
confidence: 83%
“…12 Additionally, a recent observational study identified a threefold increase in hypoglycaemiarelated hospital admissions in the 12 months following the introduction of flash glucose monitoring compared with the corresponding 12-month period 2 years earlier (1.1% vs. 0.3%, p = 0.026). 13 Improvements in HbA 1c , time in range and diabetes distress scores when combining structured education with flash glucose monitoring highlight the importance of education in harnessing the efficacy of diabetes technologies. 14 Diabetes currently accounts for an estimated 10% of the NHS budget and is predicted to rise to 17% by 2035.…”
Section: Introductionmentioning
confidence: 99%